Imeglimin Inhibits Macrophage Foam Cell Formation and Atherosclerosis in Streptozotocin-Induced Diabetic ApoE-Deficient Mice - Ji Yeon Lee; Yup Kang; Ja Young Jeon; Seung Jin Han (Cells)
Atherosclerotic cardiovascular disease is a major complication of diabetes, whose progression is significantly accelerated by hyperglycemia. Imeglimin, a novel oral antidiabetic agent, has demonstrated efficacy in glucose control; however, its role in diabetes-related cardiovascular complications has not yet been fully explored. This study aimed to investigate the effects of imeglimin on foam cell formation and atherosclerosis in the context of diabetes. THP-1 macrophages were treated with oxidized low-density lipoprotein (LDL) and high glucose to induce foam cell formation in vitro. Additionally, ApoE−/− mice with streptozotocin-induced diabetes were used to determine the effects of imeglimin in vivo by analyzing metabolic parameters and atherosclerotic plaque formation. Imeglimin inhibited macrophage-derived foam cell formation by promoting the expression of ATP-binding cassette transporters (ABC) A1 and ABCG1 and downregulating the expression of CD36. The effects of imeglimin on ABCG1 and CD36 expression regulation was mediated by AMPK. In diabetic ApoE−/− mice, imeglimin reduced the atherosclerotic plaque area, decreased fasting glucose and LDL cholesterol levels, and upregulated ABCG1 expression in the liver and aorta. These findings suggest that imeglimin may have a preventive effect on foam cell formation and a therapeutic role in atherosclerosis progression in diabetic conditions.